Dynamin-Like Proteins Are Potentially Involved in Membrane Dynamics within Chloroplasts and Cyanobacteria - Jilly, Ruven; Khan, Nadir Zaman; Aronsson, Henrik; Schneider, Dirk (Frontiers in Plant Science, 2018)
Dynamin-like proteins are a family of membrane-active proteins with low sequence identity. The proteins operate in different organelles in eukaryotic cells, where they trigger vesicle formation, membrane fusion or organelle division. As discussed here, representatives of this protein family have also been identified in chloroplasts and DLPs are very common in cyanobacteria. Since cyanobacteria and chloroplasts, an organelle of bacterial origin, have similar internal membrane systems, we suggest that dynamin-like proteins are involved in membrane dynamics in cyanobacteria and chloroplasts. Here, we discuss the features and activities of dynamin-like proteins with a focus on their potential presence and activity in chloroplasts and cyanobacteria.